2003
DOI: 10.1590/s0100-72032003000800005
|View full text |Cite
|
Sign up to set email alerts
|

Prevalência de hepatite B em parturientes e perfil sorológico perinatal

Abstract: . Particularmente no Brasil, há poucos estudos de rastreamento de hepatite B em gestantes, já que os marcadores sorológicos para hepatite B não fazem parte dos exames de rotina do pré-natal em serviços públicos.As vias de transmissão do VHB incluem contato sexual, seja hetero ou homossexual, caracterizando-a como doença sexualmente transmissível, além de possível contágio por contato com sangue ou hemoderivados infectados [5][6][7] . Merece importante destaque a transmissão vertical que, em termos mundiais, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
1
0
12

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 19 publications
1
1
0
12
Order By: Relevance
“…This disease should receive constant attention in pregnant women, as infected newborn babies present a high risk of developing chronic forms of the disease due to their immunological immaturity. 24,26,27 The frequency of anti-HCV antibodies found in this study is lower than that reported in the general population, 28,29 but is close to that observed in pregnant women. 30,31 Moreover, pregnant women, with and without seropositivity had similar mean ages.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…This disease should receive constant attention in pregnant women, as infected newborn babies present a high risk of developing chronic forms of the disease due to their immunological immaturity. 24,26,27 The frequency of anti-HCV antibodies found in this study is lower than that reported in the general population, 28,29 but is close to that observed in pregnant women. 30,31 Moreover, pregnant women, with and without seropositivity had similar mean ages.…”
Section: Discussionsupporting
confidence: 60%
“…Studies performed in several states have demonstrated frequencies ranging between 0.3% and 13%, including among pregnant women. 3,[23][24][25] Previous knowledge of the serological test results for hepatitis B in pregnant women is of extreme importance as the risks of congenital transmission increase with maternal viral load. This disease should receive constant attention in pregnant women, as infected newborn babies present a high risk of developing chronic forms of the disease due to their immunological immaturity.…”
Section: Discussionmentioning
confidence: 99%
“…É importante ressaltar o grande número de pacientes incluído (mais de 3.500) e a adequada representatividade dos centros de saúde pesquisados, abrangendo serviços públicos e privados de uma cidade de médio porte, com elevada circulação de pacientes. Em concordância com esse achado, estudos realizados em outras regiões populosas do Brasil têm descrito prevalência de HBsAg entre 0,4 e 0,8% (1,4) . .…”
Section: Realizouunclassified
“…No Brasil, devido a grande extensão geográfica e a diferenças socioculturais e econômicas acentuadas entre as regiões, a prevalência de gestantes com positividade para o AgHBs varia entre 0,4% a 3,2% (2,6,13) . Até 90% dos recém-nascidos infectados por via vertical evoluem para a hepatite crônica, podendo desenvolver complicações como cirrose e carcinoma hepatocelular, além de serem fontes de contágio para seus familiares e contactantes (4,5) .…”
Section: Discussionunclassified